Anti-cluster behavior and its mechanism during water vapor sorption in chitin and chitosan membranes - Risako Nishida; Natsumi Hirota; Kazukiyo Nagai (Carbohydrate Polymer Technologies and Applications, 2023)
Alternating petroleum-based plastics to inexhaustible natural resource-based ones is an important issue worldwide, especially for the plastic packaging application. Polysaccharides are soluble in liquid water or swelled with liquid water; thus, they have been considered unsuitable materials for this application. Hence, reports on water vapor (i.e., gas) sorption properties of polysaccharide membranes are few. Polymers are well-known to demonstrate water vapor clustering during water vapor sorption. Unlike others, anti-cluster behavior for water vapor was discovered for chitin and chitosan membranes in this study. Therefore, chitin and chitosan membranes possess resistance to moisture during storage of a package, particularly for dried food. The anti-cluster mechanism was also revealed in this study. The sorption of water vapor in both membranes was considered a 1:1 interaction between hydrophilic groups and water molecules and the manner by which water molecules act on hydrophilic groups has an order.